Obvious Surface States Connecting to the Projected Triple Points in NaCl’s Phonon Dispersion - Zhang, Li; Fang, Fang; Cheng, Lixin; Lin, Huiming; Wang, Kai (Frontiers in Chemistry, 2021)
With the development of computer technology and theoretical chemistry, the speed and accuracy of first-principles calculations have significantly improved. Using first-principles calculations to predict new topological materials is a hot research topic in theoretical and computational chemistry. In this work, we focus on a well-known material, sodium chloride (NaCl), and propose that the triple point (TP), quadratic contact triple point (QCTP), linear and quadratic nodal lines can be found in the phonon dispersion of NaCl with Fmm type structure. More importantly, we propose that the clear surface states connected to the projected TP and QCTP are visible on [001] surface. It is hoped that further experimental investigation and verification for these properties as mentioned above.